2021
DOI: 10.3390/toxics9020035
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and Health Risks Assessment of Potentially Toxic Metals and Metalloids Contaminants: A Case Study of Agricultural Soils in Qatar

Abstract: In recent years, Qatar has witnessed exponential growth in the human population, urbanization, and increased anthropogenic activities, including agriculture. Potentially toxic environmental contaminants, including metals and metalloids, are commonly found in emerging economies. At high concentrations, elements such as As, Cr, and Ni can be hazardous and may lead to various health problems in humans, including cancer. The current study measured As, Cd, Cr, Cu, Ni, Pb, V, and Zn concentrations in agricultural so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 49 publications
1
15
0
1
Order By: Relevance
“…Previously, we reported high levels (in the cultivated soil) of some of the elements studied here (Alsafran et al, 2021). The objectives of the current study were to determine the levels of As, Cd, Cr, Cu, Ni, Pb, and V in three major leafy vegetables (rocca, coriander, and parsley) grown in the same cultivated soil and evaluate the human health risks among the adult (male and female) population in Qatar.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…Previously, we reported high levels (in the cultivated soil) of some of the elements studied here (Alsafran et al, 2021). The objectives of the current study were to determine the levels of As, Cd, Cr, Cu, Ni, Pb, and V in three major leafy vegetables (rocca, coriander, and parsley) grown in the same cultivated soil and evaluate the human health risks among the adult (male and female) population in Qatar.…”
Section: Introductionmentioning
confidence: 90%
“…Another notable characteristic is that the peninsula is covered with pebbles and sand that have detached from outcropped limestone (Peng et al, 2016;Al-Sulaiti et al, 2017). While there is insufficient knowledge about lithological events in Qatar, the country's exterior predominately rests on layers of clay and limestone (Alsafran et al, 2021;Fourniadis, 2010). Earlier studies on metal(oid) remediation in Qatar's natural soil have found that the concentrations of some elements were below detection limit (Usman et al, 2019;Al-Thani and Yasseen, 2020).…”
Section: Sampling Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…The continued accumulation of potentially toxic elements (PTEs), including cadmium (Cd), lead (Pb), chromium (Cr) and arsenic (As), copper (Cu), mercury (Hg), nickel (Ni), and selenium (Se) in the environment poses a significant danger to human health and undermines global environmental sustainability efforts ( Habiba et al, 2019 ; Rizvi et al, 2019 , 2020 ; Alsafran et al, 2021 ). Anthropogenic activities due to rapid industrialization, especially from oil and gas producing industries, infrastructural development, mining, foundries, smelters, coal-burning power plants, and agricultural activities, are significant contributors that enhance the elements of hazardous pollutants in the soil ( Al-Thani and Yasseen, 2020 ; Yan et al, 2020 ; Usman et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%